Genetic analysis of the dsz promoter and associated regulatory regions of Rhodococcus erythropolis IGTS8. - Li, M Z (1996)
The dsz gene cluster of Rhodococcus erythropolis IGTS8 comprises three genes, dszA, dszB, and dszC, whose products are involved in the conversion of dibenzothiophene (DBT) to 2-hydroxybiphenyl and sulfite. This organism can use DBT as the sole sulfur source but not as a carbon source. Dsz activity is repressed by methionine, cysteine, Casamino Acids, and sulfate but not by DBT or dimethyl sulfoxide. We cloned 385 bp of the DNA immediately 5' to dszA in front of the reporter gene lacZ of Escherichia coli. We showed that this region contains a Rhodococcus promoter and at least three dsz regulatory regions. After hydrazine mutagenesis of this DNA, colonies that were able to express beta-galactosidase in the presence of Casamino Acids were isolated. Sequencing of these mutants revealed two possible regulatory regions. One is at -263 to -244, and the other is at -93 to -38, where -1 is the base preceding the A of the initiation codon ATG of dszA. An S1 nuclease protection assay showed that the start of the dsz promoter is the G at -46 and that transcription is repressed by sulfate and cysteine but not by dimethyl sulfoxide. The promoter encompasses a region of potential diad symmetry that may contain an operator. Immediately upstream of the promoter is a protein-binding domain between -146 and -121. Deletion of this region did not affect repression, but promoter activity appeared to be reduced by threefold. Thus, it could be an activator binding site or an enhancer region.